2008
DOI: 10.5194/acp-8-2595-2008
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trend of surface ozone at a regional background station in eastern China 1991–2006: enhanced variability

Abstract: Abstract. Information about the long-term trends of surface and tropospheric ozone is important for assessing the impact of ozone on human health, vegetation, and climate. Long-term measurements from East Asia, especially China's eastern provinces, are urgently needed to evaluate potential changes of tropospheric ozone over this economically rapid developing region. In this paper, surface ozone data from the Linan Regional Background Station in eastern China are analyzed and results about the long-term trends … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
153
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 235 publications
(159 citation statements)
references
References 51 publications
5
153
0
1
Order By: Relevance
“…This is caused by the extremely low levels of O 3 precursors in the closed natural background condition (Ma et al, 2002;Wang et al, 2006). The difference in O 3 concentration during the day and night showed that O 3 was produced by local photochemical reactions at this site (Crutzen et al, 1999;Xu et al, 2008). Fig.…”
Section: Calculation Of O 3 Concentration-based Indicesmentioning
confidence: 96%
“…This is caused by the extremely low levels of O 3 precursors in the closed natural background condition (Ma et al, 2002;Wang et al, 2006). The difference in O 3 concentration during the day and night showed that O 3 was produced by local photochemical reactions at this site (Crutzen et al, 1999;Xu et al, 2008). Fig.…”
Section: Calculation Of O 3 Concentration-based Indicesmentioning
confidence: 96%
“…Wang et al, 2006aT. Wang et al, , 2009Takami et al, 2006;Tu et al, 2007;Ding et al, 2008;Lin et al, 2008;Xu et al, 2008;Zhang et al, 2008;Y. Wang et al, 2011) and episodic concentrations of exceeding 100 ppbv (T. Wang et al, 2006b; Z.…”
Section: H Liao Et Al: Interannual Variations Of Summertime Surfacementioning
confidence: 99%
“…A 5-week field campaign was carried out in the early winter of 1999 at Lin'an, a background station in the Yangtze River Delta (Xu et al, 2002). However, since then the physical and chemical properties of gas and particulate pollutants have changed dramatically with the rapidly developing economy and fast growing population, e.g., from 1999 to 2013, the sulfate mass concentration decreased from 21.2 ± 11.5 to 8.1 ± 4.1 (mean ± SD) (Qi et al, 2012;Xu et al, 2008;ZEPB, 1999ZEPB, , 2013. In order to better understand the aerosol light scattering properties and their dependency on relative humidity in the Yangtze River Delta, both the scattering and backscattering coefficients under dry (RH < 40 %) conditions and controlled, elevated relative humidity were measured, along with the chemical composition and particle number size distribution.…”
Section: Introductionmentioning
confidence: 99%